The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/09297049.2017.1360854
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory in youth with perinatally-acquired HIV infection

Abstract: Youth with perinatal HIV infection (PHIV) are at increased risk for neurocognitive impairment (NCI). Prospective memory (PM) is a complex neurocognitive function that has been shown to be impaired in adults with HIV disease and independently associated with poorer daily living skills, including medication nonadherence. The current study sought to determine the presence and extent of PM deficits in youth with PHIV. Participants included 173 youth with PHIV and 85 youth perinatally HIV-exposed but uninfected (PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…106 3–5 Non-clinical - Five-year-old children were significantly better than the younger children. High level of OT’s difficulty resulted in worse PM scores, even in a high-motivation condition Harris et al, 2017 PROMACY 258 14.2 PHEU, PHIV/C, and PHIV/non-NCI NEPT, WRAML2, WISC-IV or WAIS-IV, D-KEFS PHIV/C scores were significantly lower than PHIV/non-C and PHEU on both PROMACY and NEPT scores. NEPT has presented increased sensitivity when compared to PROMACY Garvie et al, 2019 PROMACY 54 13 (2.6) PHEU NEPT, WRAML-2, WISC-IV or WAIS-IV, and D-KEFS PROMACY presents acceptable internal consistency and split-half reliability.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…106 3–5 Non-clinical - Five-year-old children were significantly better than the younger children. High level of OT’s difficulty resulted in worse PM scores, even in a high-motivation condition Harris et al, 2017 PROMACY 258 14.2 PHEU, PHIV/C, and PHIV/non-NCI NEPT, WRAML2, WISC-IV or WAIS-IV, D-KEFS PHIV/C scores were significantly lower than PHIV/non-C and PHEU on both PROMACY and NEPT scores. NEPT has presented increased sensitivity when compared to PROMACY Garvie et al, 2019 PROMACY 54 13 (2.6) PHEU NEPT, WRAML-2, WISC-IV or WAIS-IV, and D-KEFS PROMACY presents acceptable internal consistency and split-half reliability.…”
Section: Resultsmentioning
confidence: 94%
“…Despite the absent correlation between PROMACY’s scores and the naturalistic event-based prospective memory task (NEPT), children’s performance in PROMACY’s scores was associated with their own performance on IQ, RM, WM, and EF tests. A previous memory study (Harris et al, 2017 ) also combined data from PROMACY and NEPT as PM measures to evaluate 85 perinatally HIV-exposed uninfected (PHEU), 45 perinatally HIV infected with neurocognitive impairment (PHIV/NCI), and 128 perinatally HIV infected without neurocognitive impairment (PHIV/non-NCI). Even though NEPT has presented increased sensitivity when compared to PROMACY’s results, both instruments were sensitive to PHIV/NCI cognitive deficits.…”
Section: Resultsmentioning
confidence: 99%
“…The Memory and Executive Functioning substudy of PHACS assessed youth age 9-18 with PHIV and no Class C diagnosis (PHIV-NonC; n=105), PHIV and Class C diagnosis (PHIV-C; n=39), and PHEU (n=79). A series of publications [44][45][46][47] reported that, after adjustment for sociodemographic variables, adolescents with PHIV-NonC and PHEU were comparable on most measures. Those with PHIV-C performed significantly worse on visual recognition memory, some aspects of prospective memory, and inhibitory functioning.…”
Section: Adolescentsmentioning
confidence: 99%
“…Patients diagnosed with post-traumatic stress disorder (PTSD) have exhibited deteriorating PM performance [ 8 ]. A subset of younger children afflicted with prior AIDS-defining diagnosis and comorbid perinatal human immunodeficiency virus (PHIV) have exhibited PM impairment, which impacted necessary daily living skills such as the above-mentioned strict medication adherence [ 27 ]. Largely personal choices, such as drug use and abuse (i.e., Ecstasy), has been associated with more errors in both short- and long-term PM.…”
Section: Introductionmentioning
confidence: 99%